KEDUDUKAN ANAK PEREMPUAN SEBAGAI ANAK TUNGGAL DALAM SISTEM PEWARISAN PADA MASYARAKAT ADAT BALI ( The Position Of Daughter As The Only Children In The Inheritance System In Balinese Society ) - Wayan Jordi; Kahar Lahae; Sri Susyanti (Jurnal Ilmiah Advokasi, 2022)
Inheritance customary law is the rule of customary law that regulates how the inheritance or inheritance is passed on or divided from the heir to the heirs from generation to generation. Indigenous Balinese people with a patrilineal family system, causing only descendants with the status of kapurusa (male) are considered to be able to take care of and carry on family responsibilities. The problem in this research is "What is the position of a single girl in the inheritance system in Balinese indigenous peoples, and what efforts can be made for single unmarried girls to get their rights to inheritance in the inheritance system of Balinese indigenous peoples".This study aims: (1) analyze how the position of an only daughter in the Balinese traditional inheritance system is currently still in accordance with the development of Balinese indigenous peoples and the development of Balinese customary law which does not give inheritance rights to daughter. (2) Analyzing whether there are other efforts that can be made for single and unmarried girls to get a share of the inheritance of their parents. This study uses empirical legal research methods by focusing on the relationship between legal aspects and empirical reality.The results of the research show that (1) Inheritance rights for daughter in Balinese customary law are basically daughter are not heirs according to the Balinese Inheritance Law, but girls are entitled to a share of the inheritance from their parents, the procedure for granting inheritance rights for single girls to Inheritance property can become heirs by way of status changes, namely from pradana status to purusa status and marriage in the form of nyeburin. (2) For a daughter, it is possible to make various efforts in order to inherit or get a part of the inheritance from their parents, where in practice the gift is used with various terms such as tetadan treasure, grant, provision of life, pengupa jiwa and jiwa dana.Keywords: Daughter, Inheritance Rights, Balinese Customary Law.